2013
DOI: 10.1007/s00211-013-0561-5
|View full text |Cite
|
Sign up to set email alerts
|

Generalized polarization tensors for shape description

Abstract: International audienceWith each domain, an infinite number of tensors, called the Generalized Polarization Tensors (GPTs), is associated. The GPTs contain significant information on the shape of the domain. In the recent paper (Ammari et al. in Math. Comput. 81, 367–386, 2012), a recursive optimal control scheme to recover fine shape details of a given domain using GPTs is proposed. In this paper, we show that the GPTs can be used for shape description. We also show that high-frequency oscillations of the boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 24 publications
2
76
0
Order By: Relevance
“…This probably arises from the analytical model outlined in section 2.2, which estimates the electrical response of an object by its leading order dipolar component. In reality, such responses are an infinite multipolar expansion Landau and Lifshitz (1984); Ammari, Garnier, Kang, Lim and Yu (2014). In particular, the non-uniformity of the basal electric field E 0 causes further components of the multipolar response of the object that we neglect in our present model.…”
Section: Simulation Of the Music Algorithmmentioning
confidence: 99%
“…This probably arises from the analytical model outlined in section 2.2, which estimates the electrical response of an object by its leading order dipolar component. In reality, such responses are an infinite multipolar expansion Landau and Lifshitz (1984); Ammari, Garnier, Kang, Lim and Yu (2014). In particular, the non-uniformity of the basal electric field E 0 causes further components of the multipolar response of the object that we neglect in our present model.…”
Section: Simulation Of the Music Algorithmmentioning
confidence: 99%
“…In [Khairuddin andLionheart, 2016, Ammari et al, 2014], authors show that at leading order, the electric response of any shaped object can be described as that of an ellipsoid. Therefore, objects are described by ellipsoids and their electrical response are modeled analytically by their first order generalized polarization tensor [Ammari et al, 2014]. Due to experimental constraints which prevent us from measuring the object influence only (the aquarium walls were perceived by the robot because of its smallness), all experiments were performed twice with and without object to be able to remove the effects of the aquarium.…”
Section: Problem Definitionmentioning
confidence: 99%
“…3.2 Expression of the ellipse tensor [Ammari et al, 2014] As shown in [Ammari et al, 2014], at the leading order the electric response of an object can be modeled by the following tensor:…”
Section: The Analytical Model For Our Slender Robotmentioning
confidence: 99%
See 2 more Smart Citations